The Synergy of Plasmonic Enhancement and Hot‐Electron Effect on CsPbBr3 Nanosheets Photodetector. Issue 6 (1st February 2021) - Dong, Yuhui; Xu, Leimeng; Zhao, Yongli; Wang, Shalong; Song, Jizhong; Zou, Yousheng; Zeng, Haibo
Abstract: Nowadays, 2D inorganic cesium lead halide perovskites (IHPs) based photodetectors (PDs) have shown great potential due to the excellent optoelectronic properties. However, most of them only focus on improving carrier transmission and not on synergistic increase in light absorption efficiency or vice versa, limiting the total number of photon‐generated carriers. Here, an effective and general strategy is demonstrated, combining the synergy of plasmonic enhancement of light absorption and hot‐electron effect. The responsivity and external quantum efficiency (EQE) of this planar PD improves obviously, which is more than 20‐fold of the pristine devices. Furthermore, a wide linear dynamic range (LDR) of 120 dB is realized, and both response speed and operating frequency are simultaneously improved. The results present the potential use of synergistic effect for PDs, and provide a promising strategy for improving performance of perovskite optoelectronic devices. Abstract : In this work, the synergy of plasmonic enhancement and hot‐electron effect is demonstrated to efficiently improve planar perovskite photodetectors. Both responsivity and external quantum efficiency (EQE) are obviously promoted with more than 20‐fold. In addition, a large linear dynamic range of 120 dB is shown. It provides a general and effective way for elevating performance of planar optoelectronic devices.